2003
DOI: 10.1002/ar.a.10107
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptor α (ERα) in the rat temporomandibular joint

Abstract: Numerous epidemiological studies have pointed out a higher frequency of temporomandibular disorder (TMD) in women than in men, which indicates the involvement of a sex hormone, such as estrogen, in the pathogenesis of TMD. Although estrogen is known to play pivotal roles in osteoarthrosis or rheumatoid arthritis in systemic joints, there have been few reports about the role of estrogen in the temporomandibular joint (TMJ). The effect of estrogen is generally mediated by the estrogen receptors (ERs) ER␣ (the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 48 publications
1
26
0
4
Order By: Relevance
“…Previously, JM-evoked c-fos production in superficial laminae was shown to depend on RGD binding integrins in OvX females, independent of the dose of E2 replacement, whereas males were not affected (Bereiter et al 2006). ER-positive cells found in most TMJ tissues (Yamada et al 2003) may contribute to the structural effects of estrogens (Abubaker et al 1996;Yasuoka et al 2000). Also, a small but significant percentage (18%) of TMJ units in superficial laminae of males received no convergent cutaneous input ("deep-only" cells), whereas no such cells were found in OvX females.…”
Section: Estrogen Status and Mechanosensory Input To Tmj Unitsmentioning
confidence: 99%
“…Previously, JM-evoked c-fos production in superficial laminae was shown to depend on RGD binding integrins in OvX females, independent of the dose of E2 replacement, whereas males were not affected (Bereiter et al 2006). ER-positive cells found in most TMJ tissues (Yamada et al 2003) may contribute to the structural effects of estrogens (Abubaker et al 1996;Yasuoka et al 2000). Also, a small but significant percentage (18%) of TMJ units in superficial laminae of males received no convergent cutaneous input ("deep-only" cells), whereas no such cells were found in OvX females.…”
Section: Estrogen Status and Mechanosensory Input To Tmj Unitsmentioning
confidence: 99%
“…In the literature, estrogen has been shown to play an important role in the development of TMJ and temporomandibular diseases [17][18][19] . These findings have been supported by the existence of estrogen receptors (ERs) in mandibular condylar cartilage [20,21] . As an estrogen-targeted tissue [20,21] , cartilage is usually a solid connective tissue that covers subchondral bone tissue and plays an important role in the development of OA.…”
Section: Introductionmentioning
confidence: 85%
“…These findings have been supported by the existence of estrogen receptors (ERs) in mandibular condylar cartilage [20,21] . As an estrogen-targeted tissue [20,21] , cartilage is usually a solid connective tissue that covers subchondral bone tissue and plays an important role in the development of OA. To the best of our knowledge, however, few studies of the effect of genistein on cartilage have been reported, especially in vivo studies.…”
Section: Introductionmentioning
confidence: 85%
“…54,55 Estrogen receptors have been identified in TMJs of rat, baboon, and human female. [56][57][58] Estrogen receptors have also been detected in rat and human TMJs in both sexes using standard immunohistochemical approaches. 56,58 However, functional estrogen receptors were not found in TMJs obtained from male baboons, as assessed by in vivo binding of 3 H-17b estradiol.…”
Section: Sexmentioning
confidence: 99%